Activation and deactivation kinetics of oxygen reduction over a la 0.8Sr0.2Sc0.1Mn0.9O3 cathode - Zheng, Y.; Ran, R.; Shao, Zongping (American Chemical Society, 2008)
Electrochemical impedance spectroscopy, step current polarization, and cyclic voltammetry were applied to investigate the activation and deactivation kinetics of oxygen reduction over a novel La0.8Sr 0.2Sc0.1Mn0.9O3 (LSSM) cathode material. Oxygen vacancies were created after cathodic polarization for a certain period of time. The generating rate was closely related with oxygen partial pressure of surrounding atmosphere (Po2). polarization time, temperature, and voltage. The in situ created oxygen vacancies could propagate both over the surface and into the bulk of the LSSM electrode after a high cathodic polarization. Both chemical oxidation by ambient air and electrochemical oxidation by anodic polarization were exploited to demonstrate the deactivation mechanism of these in situ created oxygen vacancies. The rate-determining step of oxygen reduction reaction over LSSM electrode before and after the activation was also investigated. It was by oxygen ion surface diffusion at 800 °C in air, while a steady change to an electron-transfer process was observed with decreasing temperature and Po2. © 2008 American Chemical Society.